A High Resolution Multi-Physics Numerical Model for Planar SOFC Stack. (2nd June 2015) - Li, Ang; Fang, Xiurong; Lin, Zijing
Abstract : We report a successful development of a high space resolution multi-physics mathematical model for full scale planar SOFC stacks which is, to the best of our knowledge, the first of its kind. This 3D 30-cell stack model takes into account the coupled physical processes, applicable for both methane and hydrogen based fuels. Every cell consists of 30 channel-rib pitches, i.e., there are 900 repeating units for the electrochemically active area of the 30-cell stack. The computational domain contains all components of the stack, including channels, internal manifolds, PEN assemblies, interconnects, seals and frames. This model is constructed using the CFD software, FLUENT®, supplemented with in-house developed external subroutines to ensure all governing equations and physical properties are correctly coupled and solved successfully. Multi-physics numerical simulations of this truly high resolution computational model of 30-cell stack have been successfully performed in a 2-CPU/16-core PC.